2010
DOI: 10.1111/j.1365-2125.2010.03715.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired irinotecan biotransformation in hepatic microsomal fractions from patients with chronic liver disease

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The anticancer agent irinotecan is a prodrug that is hydrolyzed by hepatic carboxylesterase to its active and toxic metabolite SN-38 and oxidized by CYP3A4 to its inactive metabolite APC.• Irinotecan therapy is complicated by co-administered drugs that inhibit CYP3A4 and decrease APC formation and that indirectly increase SN-38 formation. • Dose adjustment in cancer patients with liver disease has been recommended. WHAT THIS STUDY ADDS• In microsomal fractions from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It has also been reported that perindopril and cilazapril hydrolysis is decreased in patients with hepatic cirrhosis and hepatitis, respectively . The metabolism of irinotecan by CYP3A4 and its hydrolysis by carboxylesterases to SN‐38 was decreased in hepatic microsomes from subjects with liver dysfunction . Such decreases in metabolic activity associated with hepatic disease are expected to occur based on the location of carboxylesterase enzymes in the endoplasmic reticulum; however, an unusual finding of increased carboxylesterase 1 levels in mice (containing human‐mouse chimeric livers) infected with hepatitis C virus suggests caution in assuming hepatic infection results in reduced enzymatic activity.…”
Section: Variability Of Hydrolysis By Hce1 and Hce2mentioning
confidence: 99%
“…It has also been reported that perindopril and cilazapril hydrolysis is decreased in patients with hepatic cirrhosis and hepatitis, respectively . The metabolism of irinotecan by CYP3A4 and its hydrolysis by carboxylesterases to SN‐38 was decreased in hepatic microsomes from subjects with liver dysfunction . Such decreases in metabolic activity associated with hepatic disease are expected to occur based on the location of carboxylesterase enzymes in the endoplasmic reticulum; however, an unusual finding of increased carboxylesterase 1 levels in mice (containing human‐mouse chimeric livers) infected with hepatitis C virus suggests caution in assuming hepatic infection results in reduced enzymatic activity.…”
Section: Variability Of Hydrolysis By Hce1 and Hce2mentioning
confidence: 99%
“…Pharmacokinetic studies have shown that considerable differences in interpatient irinotecan metabolism exist and one of the limiting factors in the efficacy of this compound is its bioactivation by CES [14]. In addition, impaired irinotecan hydrolysis in patients with chronic liver disease has been observed [15]. Furthermore, estercontaining pesticides such as pyrethroids and organophosphates (OPs) can elicit acute and developmental effects in rodents and possibly in humans [16], [17], which may be related to the hydrolytic metabolism of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, data regarding the hepatic metabolism of 9-AC is limited as only one study reported the occurrence of hepatic biotransformation products without any structural information or quantification (20). The structural analog irinotecan is inactivated by hepatic cytochrome P450 (CYP) 3A4-dependent oxidation to 7-ethyl-10-[4-N-(5-aminopentanoic acid)-1piperidino] carbonyloxy-camptothecin and when CYP3A4 metabolism is affected, dose modification of irinotecan has been shown to be necessary (21). It is therefore highly probable that 9-AC is also subject to CYP-mediated biotransformation, resulting in lower plasma levels in patients, as impairment of 9-AC serum concentrations and increased clearance have already been observed in patients receiving hepatic enzymeinducing anticonvulsant medications (22).…”
Section: Introductionmentioning
confidence: 99%